2021
DOI: 10.2147/pgpm.s324612
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Novel Biomarkers for P2Y12 – Inhibitors Resistance Prediction

Abstract: The aim of this study is to assess 6 micro-RNAs: miR-126, miR-223, miR-150, miR-29, miR-34, miR-142 as potential biomarkers for P2Y12-inhibitors resistance prediction. Methods: Eighty patients with an acute coronary syndrome undergoing percutaneous coronary intervention treated in a multidisciplinary hospital in Moscow with DAPT (either with ticagrelor, n=45, or clopidogrel, n=35) were enrolled. The carriership of 6 clinically relevant polymorphisms for ticagrelor and 17 for clopidogrel was detected. Expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Alteration in platelet aggregation due to reduced P2Y 12 expression caused by miRNA-126 inhibition was confirmed in patients with ACS [ 82 ]. In another study on that group of patients, the statistically significant connection between miRNA-29 and miRNA-34 expression levels and P2Y 12R gene polymorphism (A > G, rs3732759) was reported [ 83 ]. Syam et al [ 84 ] noticed a significant association of high miRNA-26a platelet expression but not DNA methylation of the P2Y 12 gene on platelet reactivity in patients with acute STEMI undergoing clopidogrel therapy.…”
Section: Epigenetic Studies On P2y12mentioning
confidence: 99%
“…Alteration in platelet aggregation due to reduced P2Y 12 expression caused by miRNA-126 inhibition was confirmed in patients with ACS [ 82 ]. In another study on that group of patients, the statistically significant connection between miRNA-29 and miRNA-34 expression levels and P2Y 12R gene polymorphism (A > G, rs3732759) was reported [ 83 ]. Syam et al [ 84 ] noticed a significant association of high miRNA-26a platelet expression but not DNA methylation of the P2Y 12 gene on platelet reactivity in patients with acute STEMI undergoing clopidogrel therapy.…”
Section: Epigenetic Studies On P2y12mentioning
confidence: 99%
“…A more recent study also reported that increased expression of miR-24-3p, miR-142-3p, and miR-411-3p was positively correlated with clopidogrel resistance (CR) in CAD patients ( 205 ). Similarly, miR-29, miR-34, miR-126, miR-142, and miR-223 are also reported to be novel biomarkers for P2Y12 inhibitor resistance prediction ( 206 ). Although the mechanisms of antiplatelet resistance are complex, the relationship between plasma miRNAs and platelet resistance may be explained by their regulation on platelet surface proteins.…”
Section: Introductionmentioning
confidence: 99%